2022
DOI: 10.1002/mds.29194
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Monitoring of Progressive Supranuclear Palsy using Body‐Worn Movement Sensors

Abstract: Background We have previously shown that wearable technology and machine learning techniques can accurately discriminate between progressive supranuclear palsy (PSP), Parkinson's disease, and healthy controls. To date these techniques have not been applied in longitudinal studies of disease progression in PSP. Objectives We aimed to establish whether data collected by a body‐worn inertial measurement unit (IMU) network could predict clinical rating scale scores in PSP and whether it could be used to track dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…In an open-ended, free-text survey question, one participant summarized their access to care challenges: “It was very hard to get my mother diagnosed, and there were essentially no treatments once she was. It became our job to explain PSP to most medical providers she encountered.” These clinical journeys and delays to diagnosis echo previous literature [ 4 , 5 , 13 , 14 ].…”
Section: Current State Of Affairssupporting
confidence: 83%
See 1 more Smart Citation
“…In an open-ended, free-text survey question, one participant summarized their access to care challenges: “It was very hard to get my mother diagnosed, and there were essentially no treatments once she was. It became our job to explain PSP to most medical providers she encountered.” These clinical journeys and delays to diagnosis echo previous literature [ 4 , 5 , 13 , 14 ].…”
Section: Current State Of Affairssupporting
confidence: 83%
“…Clinical trials in PSP have taught us that clinical rating scales and imaging findings detectably worsen over 6 months [ 3 ], and certain objective gait and balance measures worsen over 3 months [ 4 ]. Thus, if we do not see a patient with PSP every 3–4 months, we may be more reactive to symptoms than proactive.…”
Section: The Problemmentioning
confidence: 99%
“…As part of a larger, longitudinal study in the United Kingdom, the "OxQuip" study, Pereira et al examined longitudinal changes in motor and cognitive symptoms on clinical scales in PSP (28), and then Sotirakis et al (29) built upon this background with longitudinal monitoring of PSP with 6 body-worn, inertial measurement units (IMU) sensors ("Opals, " by APDM). Pereira analyzed the PSPRS, MDS-UPDRS 3, MOCA, and MMSE in 28 subjects with possible or probable PSP by 2017 MDS criteria (with symptom onset at an average of 1.9 years prior to enrollment, but PSP subtypes were not specified) at visits every 3 months for 18 months.…”
Section: Gait and Balance As A Biomarker Of Progression: Longitudinal...mentioning
confidence: 99%
“…The Sotrirakis and Abate studies (26,29) both suggest that wearable sensors may be important and more sensitive detectors of disease progression than the PSPRS. Both studies also found that dynamic gait parameters, rather than balance parameters, are related to disease progression.…”
Section: Gait and Balance As A Biomarker Of Progression: Longitudinal...mentioning
confidence: 99%
“…These rating scales are the current gold standard in clinical practice, but they may be insensitive to small changes in movement in early-stage patients, and can also be affected by inter-rater variability [ [5] , [6] , [7] ]. Wearable movement sensors and digital forms of assessment are becoming increasingly popular in the study of neurodegenerative diseases [ [7] , [8] , [9] , [10] , [11] , [12] , [13] ] because of their precision and objectivity, and have been shown to discriminate between healthy adults and PD patients of different disease severity [ 11 , 14 ]. Three studies have used wearable devices in de novo patients as they are started on medication, but they have only examined two or three timepoints.…”
Section: Introductionmentioning
confidence: 99%